The Nation in the Village: Anti-Bahujan Development - Herbert, Sruthi (Prabuddha: Journal of Social Equality; Vol 1 No 1 (2018), 2018)
Local governance enables decentralisation, and is thus, more empowering to citizens, it is widely believed. In this paper, I examine how the most local level activities of the state are unmistakeably influenced by the national level discourse. This, I do by inspecting the working of the ward council meetings in one ward of a village in Kerala, the lowest level of working of the local self-government bodies. I show that discourses legitimised in these local governance bodies are counterproductive to the bahujans, from the local to the national level. Hence, development pursued by these bodies, meant for empowerment through local participation, is disempowering and against the interests of the majority of the nation: the bahujans. This paper, set as it is, in Kerala, one of the few states to fully implement decentralisation, and serves as an example for states trying to strengthen it, has lessons for those interested in democratic and inclusive development.